Cost-effective removal of COD in the pre-treatment of wastewater from the paper industry - Boguniewicz Zablocka, Joanna (2020)
The present paper reveals results of research for cost-effective removal of chemical oxygen demand (COD) contained in industrial paper mill effluent. Not only process efficiency but also wastewater treatment costs are discussed. Different pre-treatment processes are applied aiming to investigate the COD removal before discharge to the municipal sewage network. The objective of this paper is to find the optimal operating conditions for the coagulation process. The effects of key operational parameters, including the type of coagulant, initial pH, temperature and coagulant dose, on COD percentage removal were investigated. The laboratory experiments confirmed the high efficiency of chemically enhanced mechanical treatment towards COD. The data obtained show that even low dose of chemicals provides sufficient COD reduction. The initial pH of the wastewater had a significant impact on the COD removal. Under the optimal operational conditions (pH = 7.5, T = 18 °C) the treatment of wastewater from paper industries by coagulation has led to a reduction of 70% COD for wastewater discharged. In terms of the investigated paper industry wastewater, polyaluminium chloride appears to be most suitable for treatment of high COD concentration. However, in an economic evaluation of requirements for wastewater treatment, operating costs and associated saving were such that PAX was more favourable.